Computer Simulation of Surface‐Initiated Controlled Radical Polymerization: Effect of Free‐Monomer Model on Brush Properties. Issue 5 (30th July 2019) - Turgman‐Cohen, Salomon; Genzer, Jan
Abstract: Monte Carlo simulation is employed using the bond‐fluctuation model (BFM) to explore the role of free‐monomer model on surface‐initiated controlled polymerization from flat substrates. Three free‐monomer models differ in two aspects: 1) their extent of excluded volume interactions between free‐monomer/polymer segments and 2) monomer availability (finite or infinite) during the simulation. In the explicit monomer (EM) model, free‐monomers behave as a single BFM‑type units. In the phantom monomer (PM) model, free‐monomers act analogously to those in the EM model but lack excluded volume interactions with the growing polymers. In the implicit monomer (IM) model, no explicit monomers are included in the simulation box; the polymers can grow as long as space is available near active chain‐ends. It is found that the breadth of the molecular weight distribution of the grown polymers decreases from EM, to PM, to IM models. With the EM model, free‐monomers are excluded from the near‐surface region, while with the PM model they are not. Due to its excluded volume interactions, the EM model tends to compress the brush against the substrate. Finally, the relaxation of the shape of a polydisperse brush after the polymerization reaction ends has been reported. Abstract : The effect of the free‐monomer model on the kinetics and dynamics of surface‐initiated polymer growth is explored using computer simulations. Free‐monomer availability and excluded‐volume interactions between free‐monomer and polymers have effects on polymerization rate, brush shape, and dispersity.